Mono-HOPE Versus Dual-HOPE in Liver Transplantation: A Propensity Score-Matched Evaluation of Early Graft Outcome - Dominik Thomas Koch; Dominik Thomas Koch; Micol Tamai; Malte Schirren; Malte Schirren; Moritz Drefs; Moritz Drefs; Severin Jacobi; Severin Jacobi; Christian M. Lange; Christian M. Lange; Matthias Ilmer; et al. (Transplant International)
Hypothermic oxygenated machine perfusion (HOPE) has become an integral technique to enhance donor graft function in liver transplantation (LiTx). This study compares early posttransplant outcomes of mono-HOPE (portal vein perfusion only) versus dual- HOPE (both portal vein and hepatic artery perfusion). A retrospective analysis was conducted on 183 LiTx recipients, with 90 receiving mono-HOPE and 93 receiving dual-HOPE grafts. Propensity Score Matching (PSM) was applied, resulting in a matched cohort of 146 patients. Primary outcomes included one-year patient and graft survival, and non-anastomotic biliary strictures (NAS). Secondary outcomes included hospital length of stay (HLS). One-year patient survival was 81.7% in the mono-HOPE and 81.7% in the dual-HOPE group, and overall survival did not differ (p = 0.990). One-year death-censored graft survival was similarly comparable (91.2% vs. 93.3%, p = 0.893). NAS were observed in 10.96% in the mono-HOPE and 8.22% in the dual-HOPE group (p = 0.574). The median HLS was 29 days for both groups. Results suggest that dual-HOPE did not significantly improve patient or graft survival, nor did it reduce NAS or HLS compared to mono-HOPE. Assuming that larger cohorts and long-term follow-up data confirm this, additional cannulation of the hepatic artery during machine perfusion in hypothermic conditions may not be beneficial.